PENERAPAN METODA FUZZY DALAM KLASIFIKASI LAHAN KRITIS BERBASIS HYDRAULIC RESPONSE UNIT (HRU) SUBDAS CISANGKUY - Bambang Setio Budianto; Muhammad Yanuar Jarwadi Purwanto; Widiatmaka Widiatmaka; Lilik Budi Prasetyo (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2018)
Various natural disasters, such as floods and landslides, are often associated with extreme weather conditions, especially rainfall, where in fact the possibility of such a disaster will be smaller if the carrying capacity of the land is still good. The decrease of land carrying capacity is often due to land use change, so that the land is not capable to perform it functions and is categorized as critical land. The decline in land carrying capacity will affect other resources, especially water resources. Anticipatory measures of natural disasters such as floods and landslides can perfectly prepared if information regarding land conditions, including land criticality, are available in detail and up to date. The classification and mapping of land criticality becomes an important component in the preparation of land rehabilitation and natural disaster prevention plans including setting the priority actions. The Minister of Forestry Regulation no P.32 / Menhut-II / 2009 concerning Procedures for Preparation of Forest and Watershed Technical Rehabilitation Plan was use as criteria for land classification and both Fuzzy and Crisp calculation methods were applied to calculate the final score. Different classification result was found in 23 HURL and comparing to actual the condition, the Fuzzy method gives more accurate result than Crisp method.